PENINGKATAN HASIL BELAJAR TEMA 9 MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTU MEDIA AUDIOVISUAL DI KELAS IV SDN PARAKAN - Akhsanul Haifa Sani; Aryo Andri Nugroho; Tri Sugiyono (JS (JURNAL SEKOLAH), 2021)
Abstract: During the pandemic, the learning outcomes of students in grade IV at SDN Parakan were quite low. This study aims to determine how to improve learning outcomes through a Problem Based learning model assisted by audio-visual media for fourth grade students at SDN Parakan on the theme 9 Kayanya Negeriku. This research is a Classroom Action Research conducted in the fourth grade of SDN Parakan. In this study carried out as many as 3 cycles with a subject of 20 children. The results of the research that have been carried out show that learning outcomes have increased every cycle. The percentage increase in the value of student learning outcomes before being given action is 40% complete KKM and the average achievement is 59.5 then in the first cycle it increases as much as 60% complete KKM with an average achievement obtained by 68.65, increasing again at cycle II as much as 75% complete KKM with an average achievement obtained of 79.3 and increased again in cycle III with KKM completeness of 90% with an average achievement obtained of 88.22. The conclusion of the learning outcomes shows that learning themes through Problem Based Learning learning models assisted by audio-visual media can improve student learning outcomes.Keywords: Learning Outcomes, PBL, Audiovisual MediaAbstrak: Pada masa pandemi, hasil belajar peserta didik di kelas IV SDN Parakan cukup rendah. Penelitian ini bertujuan untuk mengetahui bagaimana peningkatan hasil belajar melalui model Problem Based learning berbantu media audio visual siswa kelas IV SDN Parakan pada tema 9 Kayanya Negeriku. Penelitian ini merupakan Penelitian Tindakan Kelas yang dilakukan di kelas IV SDN Parakan. Dalam penelitian ini dilaksanakan sebanyak 3 siklus dengan subjek sebanyak 20 anak. Hasil penelitian yang telah dilaksanakan menunjukkan bahwa hasil belajar mengalami peningkatan setiap siklusnya. Peningkatan presentase nilai hasil belajar peserta didik sebelum diberikan tindakan yaitu sebanyak 40 % tuntas KKM dan capaian rata-rata diperoleh 59,5 kemudian pada siklus I meningkat sebanyak 60% tuntas KKM dengan capaian rata-rata yag diperoleh sebesar 68,65, meningkat kembali pada siklus II sebanyak 75% tuntas KKM dengan capaian rata-rata yang diperoleh sebesar 79,3 dan meningkat kembali pada siklus III dengan ketuntasan KKM sebesar 90 % dengan capaian rata-rata yang diperoleh sebesar 88,22. Simpulan hasil pembelajaran menunjukkan bahwa pembelajaran tema 9 Kayanya Negeriku melalui model pembelajaran Problem Based Learning berbantu media audio visual dapat meningkatkan hasil belajar peserta didik kelas IV SDN Parakan.Kata Kunci : Hasil Belajar, PBL, Media audiovisual